Distribution of two species of Asian horseshoe crabs at west coast of Sarawak's Waters, East Malaysia - A.R., Noor Jawahir; M., Samsur; M.L., Shabdin; A.R., Khairul Adha (National Institute of Oceanography and Fisheries, 2017)
Conservation of horseshoe crabs worldwide has become challenging as the number of horseshoe crabs were decreased due to human activities. Therefore, this research was designed to assess the habitat of horseshoe crabs by determining their distribution at nine different locations in west coast of Sarawak’s waters. A line transect method was used to determine species distribution where Pasir Putih Village had the highest density of T. gigas caught with of 1.72 individuals per hectare. Based on sediment analysis, T. gigas was found mainly in sandy beach of Pasir Putih Village, Pandan Beach, Sibu Laut Village, and Gerigat Beach with total organic matter and the sediment size ranging from 0.39% to 10.9% and 125 mm to 250 mm, respectively. Meanwhile, C. rotundicauda was mostly collected from mangrove area (high content silt-clay) with sediment size less than 63 mm and total organic matter ranging from 0.35% to 27.91%. The findings of this research indicated that the distribution of T. gigas and C. rotundicauda in different preferred habitat in west coast of Sarawak’s waters were influenced by the in-situ physico-chemical parameters, type of sediment, lunar cycle and spawning season.